Un nuevo testimonio sobre la pervivencia de la vida académica en la Atenas tardoantigua - Fernández Hernández, Gonzalo (Estudios humanísticos. Geografía, historia y arte, 2021)
In this article, I state the existente of the development of Grammar in Athens in a time after 529 A.D., based on a christian inscription of the Parthenon. This epigraphical testimony completes the literary sources on this respect, which refer to Theodorus of Tarsus and Gislenus of Hagenau